The path to sustainable economies in the Middle East: Monitoring the spatial spillover effect of natural resources dependence and geopolitical risk - Mohammed Alnour; Emrah Kocak (Sustainable Futures)
Despite considerable attention given to the relationship between natural resource dependence, geopolitical risk and economic growth, existing literature often neglects the spatial transmission effects of geopolitical risk and policy dynamics from neighboring regions. Therefore, this study utilizes the Spatial Durbin Model (SDM) to analyze 14 Middle Eastern countries, examining the nature and magnitude of the spatial spillover effects among geopolitical risk, natural resource rents, and economic growth using annual data from 1990 to 2021. The findings reveal significant spatial dependency among the sampled countries. Natural resources rent positively contributes to economic growth. Moreover, the spillover effect of geopolitical risk on economic growth is both significant and more pronounced. An increase in geopolitical risk in a neighboring region has a detrimental impact on economic growth in other countries.